Teatralne wojny z kontrolą medialną - Dobrowolski, Piotr (Wydawnictwo Naukowe UAM, 2007)
The title of this essay plays on words with a title of Noam Chomsky's book Media ControI and with a term War on Terror, both connected by exploring features of 'mediality' (media-reality). The author's interest lays where theatre and media clash, giving friction of potentials that is productive by differencing 'reality' and the media. He attempts to retrace the aesthetic interpretation of the mass media relationship used in theatre, starting from the similar narratives that they both employ (basing on Polish critical reception of in-yer-face theatre). Afterward he moves to a place, where the faith in an image showed onstage is undermining, to the position that counterbalances the trust placed in an onscreen, mass media reality (exploring a practice of The Wooster Group). In the conclusion appears that theatre enlarges a distance to its construct, in an opposition to the media. It is authorized to expose its own conventionality: the stage never tries to make an uncritical illusion of reality, theatre wants to set its audience free to interpret what they see; these facts evoke a natural war between theatre and the mass media.